Nguyen Thi Minh Khai: The Revolution Heroine of Vietnam (1910-1941) - Boonwanna, Thananan (Journal of Mekong Societies, 2013)
This article aims to widen the horizons of knowledge on Vietnamese studies in the Thai academic circle through the story of “Nguyen Thi Minh Khai”, a prominent Vietnamese early revolutionary female figure. The article focuses on vital roles of women, as leading members of the Vietnamese Communist Party, in the struggle for independence from France. It also deals with Nguyen Thi Minh Khai’s biography, her participation in patriotic movements between the 1920s and 1 940s, and the end of her life in 1941. Although Nguyen Thi Minh Khai passed away almost seven decades ago, she is praised and honored by the Vietnamese people for her bravery and sacrifice. The admiration is exemplified by major roads, which are named after her, in many towns and cities across the nation.